Efficacy and safety of diclofenac suppository for postoperative pain relief after diagnostic hystero-laparoscopy and dye test: A double-blind, placebo-controlled, randomized trial - Princeston C. Okam; Joseph I. Ikechebelu; George U. Eleje; Innocent C. Albert; Boniface C. Okpala; Chioma F. Okam; Louis A. Nwajiaku; Ngozi N. Joe-Ikechebelu; Chijioke O. Ezeigwe; Chisom G. Chigbo; Chigozie G. Okafor (Elsevier, 2024)
Objective: To determine the efficacy and safety of rectal diclofenac for relieving postoperative pain following diagnostic hystero-laparoscopy and dye test (dHLD). Methods: A prospective, double-blind, placebo-controlled, randomized trial was conducted among women who underwent dHLD to evaluate fertility. The women received either rectal diclofenac with intramuscular pentazocine or intramuscular pentazocine with rectal placebo for postoperative analgesia. The median pain scores at different time points were assessed as the primary outcome measures using the Numerical Rating Scale for pain. The secondary outcome measures were analgesic consumption, time at which first analgesic was requested, satisfaction with pain relief and any adverse events. Results: In total, 108 participants were analysed (54 in each group, 1:1 ratio). The median score for postoperative pain was lower for the diclofenac group compared with the placebo group at 4 h (52.53 vs 56.47; p = 0.507), 6 h (50.48 vs 58.52; p = 0.174), 8 h (51.42 vs 57.65; p = 0.296), 10 h (51.35 vs 57.65; p = 0.285) and 12 h (52.45 vs 56.55; p = 0.485) post surgery, although the difference was not significant (p > 0.05). Seventeen participants required rescue analgesia with 30 mg of pentazocine: 11 at 4 h post surgery [5 (62.5 %) vs 6 (66.7 %)], three at 6 h post surgery [2 (25.0 %) vs 1 (11.1 %)], two at 8 h post surgery [1 (12.5 %) vs 1 (11.1 %)], and one at 12 h post surgery [0 vs 1 (11.1 %)] for the diclofenac and placebo groups respectively (p = 0.713). There were no significant differences in postoperative adverse effect profiles, overall patient satisfaction, and need for rescue analgesia between the two groups (p > 0.05). Conclusions: Postoperative use of rectal diclofenac and pentazocine is safe, but did not significantly improve pain scores, patient satisfaction and need for rescue analgesia following dHLD, compared with patients who received pentazocine and placebo. While a multi-modal approach to pain relief following dHLD does not appear to be significantly beneficial, a multi-centre study is needed to confirm or refute these findings.